(untitled) (Моделювання, керування та інформаційні технології, 2019)
A set of key performance indicators (KPIs) for manufacturing operation management is introduced in the ISO 22400 standart. In this paper, a framework is introduced in order to solve the problem of dividing into types all the 38 KPIs.